ACTUATING SYSTEMS OF ELBOW REHABILITATION DEVICES - Georgiana VETRICE; Tudor DEACONESCU (Annals: Series on engineering sciences (Academy of Romanian Scientists), 2016)
Rehabilitation equipment using continuous passive motion is useful in the case of patients with posttraumatic disorders that cannot move autonomously, succeeding in both replacing the kinesiotherapist’s work and increasing patient comfort. Continuous passive motion consists in applying a slow and uninterrupted movement to injured joints. This paper presents an analysis of the current stage of the elbow rehabilitation equipment developed by the authors, based on this technique. While most devices are driven by electric motors, due to the constructive advantages of pneumatic actuating systems, lately an increase of its applicability in this field has been recorded. Keywords